Effect of benzalkonium chloride-free latanoprost ophthalmic solution on ocular surface in patients with glaucoma - Walimbe T; Chelerkar V; Bhagat P; Joshi A; Raut A (Clinical Ophthalmology, 2016)
Tejaswini Walimbe,1 Vidya Chelerkar,2 Purvi Bhagat,3 Abhijeet Joshi,4 Atul Raut4 1Walimbe Eye Clinic, 2PBMA’s H.V. Desai Eye Hospital, Pune, 3Glaucoma Clinic, M and J Western Regional Institute of Ophthalmology, Civil Hospital, Ahmedabad, 4Clinical Research Department, Sun Pharma Advanced Research Company Ltd., Mumbai, India Introduction: Benzalkonium chloride (BAK), included as a preservative in many topical treatments for glaucoma, induces significant toxicity and alters tear breakup time (TBUT). BAK-containing latanoprost, an ester prodrug of prostaglandin F2a, can cause ocular adverse events (AEs) associated with BAK. The purpose of this study was to evaluate the efficacy and safety of BAK-free latanoprost. Patients and methods: A prospective, open-label, single-arm, multicenter, 8-week study in patients with primary open-angle glaucoma or ocular hypertension taking BAK-containing latanoprost for ≥12 months was performed. Patients were switched to BAK-free latanoprost ophthalmic solution 0.005% administered once daily, and eyes were assessed after 28 and 56 days. Primary efficacy and safety variables were TBUT and treatment-emergent AEs, respectively. Results: At day 56, 40 eyes were evaluable. Mean TBUT increased significantly from baseline (3.67±1.60 seconds) to 5.03±2.64 and 6.06±3.39 seconds after 28 and 56 days of treatment with BAK-free latanoprost (P<0.0001). Ocular Surface Disease Index© (OSDI©) score also decreased significantly to 12.06±13.40 and 7.06±10.75 at 28 and 56 days, respectively, versus baseline (18.09±18.61, P<0.0001). In addition, inferior corneal staining score decreased significantly to 0.53 from baseline (0.85, P=0.0033). A reduction in conjunctival hyperemia and intraocular pressure was observed at both time points. No treatment-related serious AEs were evident and 12 (26.08%) treatment-emergent AEs occurred in seven patients, with eye pain and irritation being the most frequent. No clinically significant changes in vital signs or slit lamp examinations were observed. Conclusion: Results indicate that switching from BAK-containing latanoprost to BAK-free latanoprost resulted in significant improvements in TBUT, OSDI© score, and inferior corneal staining score, and measurable reductions in conjunctival hyperemia score. Furthermore, BAK-free latanoprost was well tolerated with only mild-to-moderate and self-limiting AEs. BAK-free latanoprost appears to be effective in protecting ocular surface integrity in glaucoma patients but further studies are needed to confirm this beneficial effect. Keywords: tear breakup time, TBUT, Ocular Surface Disease Index, OSDI©, inferior corneal staining score, conjunctival hyperemia, intraocular pressure, glaucoma, ocular surface